2013
DOI: 10.2169/internalmedicine.52.8496
|View full text |Cite
|
Sign up to set email alerts
|

Surgically Proven Normocalcemic Primary Hyperparathyroidism: Speculation of the Possible Role of Estrogen in the Etiology of this Disease in Premenopausal Women

Abstract: We herein report a rare case of surgically proven normocalcemic primary hyperparathyroidism (NCHPT). A premenopausal 51-year-old woman was referred to our clinic because parathyroid adenoma was detected on neck ultrasonography (US). The patient's serum calcium concentration was 9.3 mg/dL and the intact parathyroid hormone (PTH) level was 128.8 pg/mL. The findings of almost all other examinations were also compatible with a diagnosis of NCHPT. Then, parathyroidectomy was performed. The serum calcium and PTH con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…21 Tachibana et al suggested that estrogen plays a role in the pathogenesis of normocalcemic primary hyperparthyroidism in premenopausal women by regulating calcium supply from bone. 22 In our study, all of the patients with PA were female and had hypercalcemia, only two patients were in menopause. However, our study design was not planned to establish a relationship between estrogen and calcium levels.…”
Section: Discussionmentioning
confidence: 54%
“…21 Tachibana et al suggested that estrogen plays a role in the pathogenesis of normocalcemic primary hyperparthyroidism in premenopausal women by regulating calcium supply from bone. 22 In our study, all of the patients with PA were female and had hypercalcemia, only two patients were in menopause. However, our study design was not planned to establish a relationship between estrogen and calcium levels.…”
Section: Discussionmentioning
confidence: 54%
“…Specific repletion recommendations are not available from clinical trial data. Until such information becomes available, cautiously repleting vitamin D in patients with underlying hyperparathyroidism is recommended since worsening hypercalcemia and hypercalciuria have been reported [8]- [14].…”
Section: Discussionmentioning
confidence: 99%